The Effect of Using Dictation Technique on The Students’ Ability in Writing Descriptive Text at Grade VII of SMP Negeri 7 Pematangsiantar - Ravika Siregar; Bloner Sinurat; Yanti Kristina Sinaga (The Future of Education Journal, 2024)
This research aimed to assess the impact of dictation techniques on the ability of students in class VII to write descriptive texts at SMP Negeri 7 Pematangsiantar. The theoretical framework was based on the work of Macon, Bewell, and Vogt. A quantitative research methodology was employed for this study. The population consisted of class VII students at SMP Negeri 7 Pematangsiantar during the 2024/2025 academic year. The researcher selected two classes as samples: VII-1 served as the experimental group with 32 students, while VII-2 acted as the control group, also comprising 32 students. The experimental group received instruction using the dictation technique, whereas the control group continued with conventional teaching methods. Data were collected through pre-tests and post-tests administered to both groups. The average score for the experimental group in the pre-test was 67.46, while the control group had an average score of 68.125. Conversely, the average score for the experimental group in the post-test rose to 84.31, compared to 82.15 for the control group. To gather data, the researcher utilized tests as instruments. The t-test result of 3.00 exceeded the t-table value at a significance level of 5% (1.670). The significance value indicated that the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. This finding suggests that the dictation technique significantly influenced the writing abilities of grade VII students at SMP Negeri 7 Pematangsiantar in composing descriptive texts.